Stage specific functional roles of integrins in erythropoiesis - Ulyanova, Tatyana (2014)
When the erythroid integrins α5β1 and α4β1 were each deleted previously at the stem cell level, they yielded distinct physiologic responses to stress by affecting erythoid expansion and terminal differentiation or only the latter, respectively. To test at what stage of differentiation the integrin effects were exerted, we created mice with α4 or α5 integrin deletion only in erythroid cells and characterized them at homeostasis and after Phenylhydrazine (PHZ)-induced hemolytic stress. The phenotype of mice with α5-erythroid deletion unlike our prior data was similar to controls, especially post-stress, and these outcomes seem to reconcile divergent prior views on its role in erythropoiesis. By contrast, α4 integrins, whether deleted early or late, have a dominant effect on bone marrow (BM) retention of erythroblasts and on terminal erythroid maturation at homeostasis and post stress.